PERILAKU STICKY COST PADA BIAYA PENJUALAN, ADMINISTRASI DAN UMUM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2012) - Risvia Apriliawati; Yeterina Widi Nugrahanti (Universitas Ahmad Dahlan, 2015)
The objective of this study is to fi nd the indication of sticky cost behavior inIndonesian manufacturing companies during 2009-2012 and prove whether the levelof sticky cost infl uenced by the economic level. The cost stickiness can be indicated byasymetric reaction of costs to changes. The samples of this study are 309 companies.For testing the hypothesis, this study use linear regression method. This study foundthat selling, general and administrative cost increase 0,117 percent when sales increase 1 percent.Whereas, the sales and selling, general and administrative cost decrease0,049 percent per1 percent decrease in sales. This researc also found that the degree ofstickiness increase during macroeconomic growth.